Perceived Threat, Reactive Identification, and Religious Change: Right-Wing Secularization in Germany, 1999–2017 - Albanese, Anthony (Religions, 2023)
In this article, I integrate symbolic threat dynamics into a theoretical discussion of religious change. Specifically, this article demonstrates how symbolic threat can lead to increases in salient collective characteristics among members of the threatened group. To make this case, I examine the religious and historical idiosyncrasies of East and West Germany. In the context of East Germany, I find a dramatic reduction in religious activity among the right-wing between 1999 and 2017, as well as a strong relationship between secularity and fear of foreign domination. Mediated by the deeply atheistic history of East Germany, secularization is here presented as a reaction of eastern identification that repeatedly emerges in the face of cultural threat. To empirically illustrate my theoretical contentions, I rely on survey data from the European Values Study (EVS) and German General Social Survey (ALLBUS).